Risk Management Strategies in Agribusiness - Loso Judijanto (Maneggio, 2025)
Production risk management is a crucial aspect in optimizing production output. This study aims to: 1) Examine the various factors affecting salak farming production in Sleman Regency; 2) Analyze the level of production risk as well as the aspects affecting the risk in salak farming in the area; 3) Develop a suitable risk management strategy to be applied to salak farming in Sleman Regency. This research involved 30 salak farmers in Bangunkerto Village, Turi Subdistrict, Sleman Regency, with interviews conducted in October 2021. Components affecting production and risk of salak pondoh farming were analyzed using multiple regression with the Ordinary Least Square model, while the level of risk was analyzed through the coefficient of variation. The results showed that the variables of organic fertilizer, number of workers, farming experience, plant age, and number of clumps had a significant effect on production. On the other hand, organic fertilizer and crop age were found to have the potential to reduce production risk.